Asymmetric Hybrid Polymer–Lipid Giant Vesicles as Cell Membrane Mimics. Issue 1 (5th December 2017) - Peyret, Ariane; Ibarboure, Emmanuel; Le Meins, Jean‐François; Lecommandoux, Sebastien
Abstract: Lipid membrane asymmetry plays an important role in cell function and activity, being for instance a relevant signal of its integrity. The development of artificial asymmetric membranes thus represents a key challenge. In this context, an emulsion‐centrifugation method is developed to prepare giant vesicles with an asymmetric membrane composed of an inner monolayer of poly(butadiene)‐ b ‐poly(ethylene oxide) (PBut‐ b ‐PEO) and outer monolayer of 1‐palmitoyl‐2‐oleoyl‐ sn ‐glycero‐3‐phosphocholine (POPC). The formation of a complete membrane asymmetry is demonstrated and its stability with time is followed by measuring lipid transverse diffusion. From fluorescence spectroscopy measurements, the lipid half‐life is estimated to be 7.5 h. Using fluorescence recovery after photobleaching technique, the diffusion coefficient of 1, 2‐dioleoyl‐ sn ‐glycero‐3‐phosphoethanolamine‐ N ‐(lissamine rhodamine B sulfonyl) (DOPE‐rhod, inserted into the POPC leaflet) is determined to be about D = 1.8 ± 0.50 μm 2 s −1 at 25 °C and D = 2.3 ± 0.7 μm 2 s −1 at 37 °C, between the characteristic values of pure POPC and pure polymer giant vesicles and in good agreement with the diffusion of lipids in a variety of biological membranes. These results demonstrate the ability to prepare a cell‐like model system that displays an asymmetric membrane with transverse and translational diffusion properties similar to that of biological cells. Abstract : Cell‐sized biomimetic vesicles with an asymmetric lipid/polymer membrane are generated from an emulsion/centrifugation method. Lipid transverse and lateral diffusion kinetics as studied via fluorescence quenching assays and confocal microscopy reveals consistent similarity to cells.